Adolescents’ Anxieties and Conflicts: A Study of Ruskin Bond’s Work: Exploring Adolescents' Anxieties and Conflicts in Ruskin Bond's Work (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This research deals with the adolescents’ anxieties and conflicts which are experienced by them during their journey, as they mature from challenging adolescence to the ultimate doom of adulthood. It will also portray that how it is useful for the evolutionary process of an adolescent in particular and mankind in general. The research has explored mainly the vital stage of adolescents and their growth and development through the various stages of human life, namely Infancy, Childhood, Adolescence and Adulthood. Through these phases of life one has to complete its life’s journey which is from infancy to adulthood and maturity, from dependency to responsibility and own authority, from self-effacement to involvement with others and from exclusivity to cultural hybridity.